2022
DOI: 10.3390/ph15050624
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nuclear Receptors in Lung Cancer—Novel Therapeutic Prospects

Abstract: Lung cancer, the second most commonly diagnosed cancer, is the major cause of fatalities worldwide for both men and women, with an estimated 2.2 million new incidences and 1.8 million deaths, according to GLOBOCON 2020. Although various risk factors for lung cancer pathogenesis have been reported, controlling smoking alone has a significant value as a preventive measure. In spite of decades of extensive research, mechanistic cues and targets need to be profoundly explored to develop potential diagnostics, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 395 publications
(439 reference statements)
0
7
0
Order By: Relevance
“…RGX-104 was observed to inhibit cellular proliferation, inducing the apoptotic signals, inhibiting MDSCs, and also sensitizing to radiotherapy with reduced immunosuppressive events ( Liang and Shen, 2020 ). Collectively, it was observed that the combination of LXR agonists with other antineoplastic agents has a potent effect against tumor growth and proliferation, and does not have a significant effect when treated alone ( Gangwar et al, 2022 ).…”
Section: Lxrs In Cancermentioning
confidence: 99%
“…RGX-104 was observed to inhibit cellular proliferation, inducing the apoptotic signals, inhibiting MDSCs, and also sensitizing to radiotherapy with reduced immunosuppressive events ( Liang and Shen, 2020 ). Collectively, it was observed that the combination of LXR agonists with other antineoplastic agents has a potent effect against tumor growth and proliferation, and does not have a significant effect when treated alone ( Gangwar et al, 2022 ).…”
Section: Lxrs In Cancermentioning
confidence: 99%
“…Many studies have revealed both tumor-suppressive and oncogenic roles of FXR in CRC [ 35 , 42 , 43 , 100 , 322 ]. The FXR expression increased with the degree of differentiation in HT-29 and Caco2 cells, and it was also demonstrated that the FXR was downregulated in colon carcinomas and adenomas [ 101 ].…”
Section: Nuclear Receptors In Colorectal Cancermentioning
confidence: 99%
“…Later, numerous studies stated the critical role of NRs in cancer development and progression [ 38 41 ]. Thus, NRs have emerged as novel, highly efficacious therapeutic targets for various malignancies [ 35 , 42 44 ]. It has also been observed that nuclear hormone receptors (NHRs) play a crucial role in interacting with hormonal factors in the nucleus and regulation of gene expression [ 36 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [ 38 , 49 ]. An accumulating number of studies have proved the significant role of NRs in the management of different hallmarks of cancers [ 38 , 50 , 51 ]. FDA-approved drugs, like toremifene, raloxifene, and bicalutamide, are designed to target NRs for the treatment of different malignancies [ 52 55 ].…”
Section: Introductionmentioning
confidence: 99%